Nature Republic dan Innisfree Sebagai Soft Power Brand Ambasador and Personality Korea Selatan di Indonesia - Aditya Putra Pratama (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
Brand Ambassador is an instrument of achieving the interests of the state which is popularly used South Korea as one example of countries that use their Brand Using (Hallyu) as the mediums to get achieved success in Indonesia. in 2002, Indonesia began to look at South Korea by showing Korean drama with the introduction of Korean drama in Indonesia through private television. The reason for the development of Korean pop culture (Korean Wave) in Indonesia is the embodiment of globalization. In the communication and cultural dimensions, South Korea is increasingly recognized by the Indonesian public drama that aired in Indonesia became the gateway for the entry of other Korean cultural products or known by the name Hallyu / Korean Wave, such as Korean pop music (K-Pop), Korean food (K-Food ), and Korean language and letters (Hangeul). It also makes many products made in Korea also enter Indonesia, including cosmetics, automotive, electronics, etc. As a form of Korean Nation Brand in Indonesia. So, Indonesian people can feel about (Hallyu) that came in. The purpose of this study will look at how Indonesia's attitude in responding to it and what is driving Indonesia's response to the phenomenon of Korean Skincare that uses as Diplomacy in Indonesia.